Innovative methodology of training of kayakers 10-11 years - Matnazarov, X.: Ikramov, B.; Azimov, Z. (Academic Research in Educational Sciences, 2022)
The article is devoted to the study of the possibilities of increasing the efficiency teaching the technique of rowing on a kayak. The authors have developed a teaching methodology, including the use of a fitball, a barefoot and a KAYAKRO rowing machine. Analysis research results showed that the innovative methodology allowed improve balance performance, technical skills, and promoted growth sports results in kayaking.